Activation of an interleukin 1 converting enzyme-dependent apoptosis pathway by granzyme B. - Shi, L (1996)
Cytotoxic T lymphocytes (CTL) can induce apoptosis through a granzyme B-based killing mechanism. Here we show that in cells undergoing apoptosis by granzyme B, both p45 pro-interleukin 1 beta converting enzyme (ICE) and pro-CPP32 are processed. Using ICE deficient (ICE -/-) mice, embryonic fibroblasts exhibit high levels of resistance to apoptosis by granzyme B or granzyme 3, while B lymphoblasts are granzyme B-resistant, thus identifying an ICE-dependent apoptotic pathway that is activated by CTL granzymes. In contrast, an alternative ICE-independent pathway must also be activated as ICE -/- thymocytes remain susceptible to apoptosis by both granzymes. In ICE -/- B cells or HeLa cells transfected with mutant inactive ICE or Ich-1S that exhibit resistance to granzyme B, CPP32 is processed to p17 and poly(ADP-ribose) polymerase is cleaved indicating that this protease although activated was not associated with an apoptotic nuclear phenotype. Using the peptide inhibitor Ac-DEVD-CHO, apoptosis as well as p45 ICE hydrolysis are suppressed in HeLa cells, suggesting that a CPP32-like protease is upstream of ICE. In contrast, p34cdc2 kinase, which is required for granzyme B-induced apoptosis, remains inactive in ICE -/- B cells indicating it is downstream of ICE. We conclude that granzyme B activates an ICE-dependent cell death pathway in some cell types and requires a CPP32-like Ac-DEVD-CHO inhibitable protease acting upstream to initiate apoptosis.